2022
DOI: 10.1021/acs.nanolett.2c00289
|View full text |Cite
|
Sign up to set email alerts
|

Implantable Aptamer-Graphene Microtransistors for Real-Time Monitoring of Neurochemical Release in Vivo

Abstract: The real-time monitoring of neurochemical release in vivo plays a critical role in understanding the biochemical process of the complex nervous system. Current technologies for such applications, including microdialysis and fast-scan cyclic voltammetry, suffer from limited spatiotemporal resolution or poor selectivity. Here, we report a soft implantable aptamer-graphene microtransistor probe for real-time monitoring of neurochemical release. As a demonstration, we show the monitoring of dopamine with nearly ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…56 Previous histological studies have shown that polyimide devices of similar thickness and bending stiffness induce minimal immune responses. 30,40 Note that the width of the probes and FETs can be scaled down in a straightforward manner to 50 μm using photolithography, as we have previously demonstrated using Si as the device substrate. 4 Polyimide is thermally stable and compatible with most microfabrication processes up to 350 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…56 Previous histological studies have shown that polyimide devices of similar thickness and bending stiffness induce minimal immune responses. 30,40 Note that the width of the probes and FETs can be scaled down in a straightforward manner to 50 μm using photolithography, as we have previously demonstrated using Si as the device substrate. 4 Polyimide is thermally stable and compatible with most microfabrication processes up to 350 °C.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Recently, Zhang and co-workers developed graphene-based aptamer-FET biosensors using our aptamers for dopamine and serotonin sensing. 29,30 To monitor neurotransmitters in vivo, we developed Si-based implantable neuroprobes with miniaturized aptamer-FET biosensors. Probes were either 150 or 50 μm in width and thickness at the tips.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Any other nanostructures should keep being optimized to meet these standards. In addition, the use of these nanotherapies could be complemented with the administration of nanosensors selective to DA and capable of measuring in real-time and at a cellular scale the variations in the concentrations and release kinetics of the neurotransmitter [ 308 , 309 ]. Thus, the impact of the applied nanostructures on the neurological disease-related processes of the patient could be monitored and, thus, the therapy adapted in a tailored manner with respect to the prognosis of the patient.…”
Section: Perspectives On Nanomedicine-based Therapies For Parkinson’s...mentioning
confidence: 99%
“…However, the large device size and bulky and rigid component materials lead to constrained spatial resolution and potential brain tissue damage, limiting its practical application in in vivo studies. Recently, implantable aptamer-modified field-effect transistors were reported for monitoring serotonin or dopamine in vivo. , Although these studies represent significant progress for individual neurotransmitter monitoring, like dopamine or serotonin, it is still challenging to achieve simultaneous monitoring of different types of neurochemicals with spatiotemporal precision and molecular specificity.…”
Section: Introductionmentioning
confidence: 99%